Grasshopper Plague Control in the Alpine Rangelands of the Qilian Mountains, China. A Socio‐Economic and Biological Approach. (10th February 2016) - Sun, Tao; Liu, Xiaoli; Sun, Guojun; Long, Ruijun; Liu, Zhiyun
Abstract: The probability and frequency of grasshopper plague outbreaks in the alpine rangelands of China have greatly increased since the middle of the last century, adversely affecting grassland ecosystems and the livelihood of herders. We propose that herders could use poultry to forage on grasshoppers to control plague. Here, we investigated the proximate (application in 2007) and persistence (continued effects across 2008–2011) effects of three different control agents (foraging chickens, a broad spectrum insecticide Beta‐Cypermethrin and an entomopathogenic fungus Metarhizium ) on grasshopper population density. The comparative effectiveness of the three control agents was assessed by calculating grasshopper mortality and nymph:adult ratios. Subsequently, we examined the efficiency of chicken foraging activity at controlling grasshopper numbers under various levels of outbreaks. Finally, we used a cost–benefit analysis to assess the economic benefits of a traditional sheep rearing system versus a system that includes chicken rearing. In the first year, all three agents were initially effective at reducing grasshopper densities, but only chickens generated a persistence effect (lasting up to 5 years). Overall, chickens also provided the greatest economic benefits to herders than the other two control agents. Using foraging chickens to suppress grasshopper infestation in the alpine rangelands of China provides a novel approach toward mitigating outbreaks. Copyright © 2016 John Wiley & Sons, Ltd.